A Retrospective 3D Radiologic Analysis of 52 Patients with Mandible Fractures - Özkan, Heval Selman; Irkoren, Saime; Durum, Yasemin; Karaca, Can (Facial Plastic Surgery, 2016)
When fractured, mandible angulates. For better preoperative evaluation, movements of fractured mandibular segments should be documented in x-, y-, and z-axes. This article quantitatively evaluates the pattern and degree of the angulation. Fifty-two patients with mandible fractures were involved in this study. After defining a three-dimensional (3D) coordination system consisting of the x-axis (the axis directed from the medial to lateral side of the skull), y-axis (directed from the inferior to superior side), and z-axis (directed from the posterior to anterior side), the degree with which the fractured mandible angulated around each of these axes was measured using 3D graphic software. The tendency of the angulation was compared between the three axes. Frequency of complications, operation times, maxilla mandibular fixation (MMF) need, and epidemiologic data were compared with the angulation results. Angulation around the x-axis was the most frequent with a 55.8% incidence, followed by a substantial margin of angulation around the y-axis with a 21.2% incidence; angulation around the z-axis was rare, with an incidence of 15.4%. Furthermore, the degree of z-axis angulation was minor compared with x- and y-axes angulations. There were statistically increased rate of complications, operation time, and MMF need in patients with more than 10 degrees of angulation in any case. Operation time and complication rates are also increased in patients with internal rotation of the proximal segment. Preoperative evaluation of mandible fracture angulation degree is useful for determining postoperative complication rates, MMF need, and operative challenge. This finding is helpful for effective performance to reposition the fractured mandible.
Keywords: 3D CT; mandibular fractures; radiologic analysis